2013
DOI: 10.1007/s10661-013-3178-3
|View full text |Cite
|
Sign up to set email alerts
|

Plankton diversity and water quality assessment of three freshwater lakes of Mandi (Himachal Pradesh, India) with special reference to planktonic indicators

Abstract: The present study deals with the limnobiotic status of three selected lakes of Himachal Pradesh using physicochemical and biological parameters (especially phytoplankton and zooplankton) over a period of 2 years. One hundred forty-eight species belonging to nine groups of phytoplankton and 79 species belonging to five groups of zooplankton were identified from the lakes. Trophic level and the pollution status of the lakes were assessed upon the basis of Shannon diversity index (H'), species richness index (S),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
71
2
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 25 publications
14
71
2
12
Order By: Relevance
“…The biodiversity of phytoplankton in Nansi Lake remained steady in 2014, which indicated that worse water quality had little influence on the biodiversity of phytoplankton in a short time. But in 2015, biodiversity of phytoplankton in Nansi Lake decreased significantly, which may due to the increase in eutrophication [27][28]. Worse water quality resulted in lower zooplankton density of some species, while richness of zooplankton did not change in our study.…”
Section: Annual Dynamics Of Plankton and Zoobenthosmentioning
confidence: 65%
“…The biodiversity of phytoplankton in Nansi Lake remained steady in 2014, which indicated that worse water quality had little influence on the biodiversity of phytoplankton in a short time. But in 2015, biodiversity of phytoplankton in Nansi Lake decreased significantly, which may due to the increase in eutrophication [27][28]. Worse water quality resulted in lower zooplankton density of some species, while richness of zooplankton did not change in our study.…”
Section: Annual Dynamics Of Plankton and Zoobenthosmentioning
confidence: 65%
“…Nilai DO perairan Situ Gintung pada kedua musim memiliki kisaran yang sama dengan penelitian sebelumnya di danau Mandi India pada musim panas hingga musim dingin dengan nilai 3-13 mg.L -1 (Thakur et al, 2013), lebih rendah dari nilai DO di Situ Lembang pada musim kemarau yang mencapai 10 mg.L -1 (Sulastri, 2011). DO perairan Situ Gintung memiliki korelasi positif dengan temperatur dan pH di kedua musim (Table 2).…”
Section: H a S I L D A N P E M B A H A S A Nunclassified
“…Hasil pengukuran TDS di perairan danau Situ Gintung memiliki kisaran yang sama dengan penelitian sebelumnya di danau Mandi India pada musim panas sampai musim dingin dengan nilai 76-296 mg.L -1 (Thakur et al, 2013). TDS di ekosistem perairan dipengaruhi musim, temperatur (Celik & Ongun, 2007), dan pengaruh aktifitas manusia (Thakur et al, 2013).…”
Section: H a S I L D A N P E M B A H A S A Nunclassified
See 1 more Smart Citation
“…The planktonic study is a very useful tool for the assessment of water quality and productivity of any (Pawar et al, 2006). When an aquatic ecosystem is considered, the planktons prove to be of great importance as the changes in the environment can portray an instantaneous response of the planktons (Thakur et al, 2013 andMalik et al, 2013). The plankton growth rate and development depends on various biotic as well as abiotic factors like, light, temperature, available nutrients, hydronamics, predation, oxygen concentration, pH, etc (Dhar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%